Thodisiso ya vhungoho nga ha zwine ha pfi zwiambaro zwa vhafumakadzi zwa sialala zwi na mulaedza une zwa u pfukisela vhathuni musi vho zwi ambara :|bhu tshi do lavheleswa kha Tshitiriki tsha Vembe vunduni la Limpopo - Mushaisano, Azwindini Winnie (My University, 2009)
The study evaluates the communicative aspects of the Vhavenḓa female traditional attire in the Vhembe region, Limpopo Province. Chapter one carries an introduction and background to the study, aim of the study, rationale and objectives of the study, significance of the study, literature related to the study and data analysis thereof. Chapter two carries the detailed investigation of the Vhavenḓa Traditional attire as well as the relevant times to wear that attire, where and their uses. Chapter three carries the Vhavenḓa Traditional attires that are not allowed to be worn in some occasions. Chapter four carries the findings and the recommendations of the study. Chapter five is the summary of the study.
Thesis (M A. (African Languages)) -- University of Limpopo, 2009
Keywords: Venda traditional attire; Ethnic costume; Women's clothing - Symbolic aspects